Haptic Augmentation of the Hybrid Piano. - Hayes, Lauren (Contemporary Music Review, 2013)
One of the most vital feedback systems that has been embedded in musicians for centuries is that of physical response. In the same way that auditory information is available and used throughout a performance, a musician will continuously reassess their playing by making use of not only their specialised sensorimotor skills, but also the tangible feedback that is relayed to them through the body of the instrument. This paper discusses approaches to the development of an augmented instrument, namely the hybrid piano, which focuses on the notion of performance as perceptually guided action. While the acoustic component of the sound energy of the augmented instrument is created within the real-world interactions between hammers, resonating strings, and the soundboard, the digital sonic events cannot be located in a similar palpable source. By exploring notions of multimodality and haptic feedback, the ongoing processes of human action and perception within instrumental performance can be maintained for the player, whilst arguably, also enhancing the experience for the listener.